2023
DOI: 10.1073/pnas.2218949120
|View full text |Cite
|
Sign up to set email alerts
|

Human brain effects of DMT assessed via EEG-fMRI

Abstract: Psychedelics have attracted medical interest, but their effects on human brain function are incompletely understood. In a comprehensive, within-subjects, placebo-controlled design, we acquired multimodal neuroimaging [i.e., EEG-fMRI (electroencephalography-functional MRI)] data to assess the effects of intravenous (IV) N,N-Dimethyltryptamine (DMT) on brain function in 20 healthy volunteers. Simultaneous EEG-fMRI was acquired prior to, during, and after a bolus IV administration of 20 mg DMT, and, separately, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
71
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 98 publications
(93 citation statements)
references
References 90 publications
5
71
0
Order By: Relevance
“…This popular ‘meme’ likely has its origin in the first resting-state fMRI study of a psychedelic, where decreased blood flow, BOLD signal and altered FC were observed in a pattern of regions resembling the DMN (Carhart-Harris et al, 2012). Eleven years later, evidence continues to indicate that psychedelics potently affect the regularity of population brain activity in DMN regions (Timmermann et al, 2023). Since a commonly reported experience on psychedelics is the dissolution of the self, a phenomenon known as “ego death” (Moreton et al, 2020; Nour et al, 2016; Pahnke, 1969b), it would superficially make sense that psychedelics dysregulate the DMN.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This popular ‘meme’ likely has its origin in the first resting-state fMRI study of a psychedelic, where decreased blood flow, BOLD signal and altered FC were observed in a pattern of regions resembling the DMN (Carhart-Harris et al, 2012). Eleven years later, evidence continues to indicate that psychedelics potently affect the regularity of population brain activity in DMN regions (Timmermann et al, 2023). Since a commonly reported experience on psychedelics is the dissolution of the self, a phenomenon known as “ego death” (Moreton et al, 2020; Nour et al, 2016; Pahnke, 1969b), it would superficially make sense that psychedelics dysregulate the DMN.…”
Section: Discussionmentioning
confidence: 99%
“…While these latter findings about RSN disintegration and desegregation have been replicated across time, DMN-specific deactivation has not, and the initial focus on the DMN now seems unjustified. In more recent work by Carhart-Harris and colleagues, greater emphasis has been placed on the dysregulation of spontaneous activity across the high-level transmodal cortex, of which the DMN is a part (Girn et al, 2023; Timmermann et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As the scientific and clinical interest in psychedelics continues to grow, there is a pressing need for a deeper neurobiological understanding. Although there are extensive neuroimaging studies on the neural correlates of classical serotonergic psychedelics-such as lysergic acid diethylamide (LSD), psilocybin, and dimethyltryptamine (DMT) (Carhart-Harris et al, 2012Timmermann et al, 2023)-nitrous oxide remains relatively understudied, despite the longstanding recognition of its psychedelic effects (Block et al, 1990;James, 1874).…”
Section: Introductionmentioning
confidence: 99%